2003
DOI: 10.1051/rnd:2003030
|View full text |Cite
|
Sign up to set email alerts
|

Whole body glucose turnover in growing and non-productive adult ruminants: meta-analysis and review

Abstract: -The objectives of the present paper were to review and quantitatively determine the influence of the nutritional factors on whole body glucose turnover in growing and adult non-productive ruminants. A meta-analysis approach was used. The dietary grain: forage ratio significantly increased the slope of the relationship between glucose turnover and metabolisable energy intake. This effect was probably associated with the inclusion of maize rather than any other grain source in the diet. The analysis pointed out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
10
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 63 publications
7
10
0
1
Order By: Relevance
“…It was closer to values predicted for growing bovines than to values predicted for adult ovines [40] given the plane of feeding applied. It was also closer to the values predicted for adult ovines fed concentrate based diets than forage based diets [40].…”
Section: Whole Body Glucose Turnover With the Control Dietsupporting
confidence: 49%
See 1 more Smart Citation
“…It was closer to values predicted for growing bovines than to values predicted for adult ovines [40] given the plane of feeding applied. It was also closer to the values predicted for adult ovines fed concentrate based diets than forage based diets [40].…”
Section: Whole Body Glucose Turnover With the Control Dietsupporting
confidence: 49%
“…It was closer to values predicted for growing bovines than to values predicted for adult ovines [40] given the plane of feeding applied. It was also closer to the values predicted for adult ovines fed concentrate based diets than forage based diets [40]. Only one other study reported glucose turnover data with grass diets being fed to adult non producing ewes [41], the results were close to the values predicted for concentrate based diets [40].…”
Section: Whole Body Glucose Turnover With the Control Dietsupporting
confidence: 49%
“…The inconsistency of effects of supplemental propionate on blood glucose metabolism may be involved in the dose, duration or method of propionate supplementation, the stage of animals, or feeding managements. Although basal blood GTR was within the ranges of blood GTR as determined by the isotope dilution methods using stable and radio isotopes, blood GTR for the Prop diet seemed to be near the upper margin [12,18,28,29]. Because blood GTR is influenced by the type of diet, energy intake and physiological status [28][29][30], these factors may be related.…”
Section: Discussionmentioning
confidence: 85%
“…Although basal blood GTR was within the ranges of blood GTR as determined by the isotope dilution methods using stable and radio isotopes, blood GTR for the Prop diet seemed to be near the upper margin [12,18,28,29]. Because blood GTR is influenced by the type of diet, energy intake and physiological status [28][29][30], these factors may be related. OrtiguesMarty et al [29] reviewed the relationship between glucose turnover rate and ME intake in growing ovines, growing bovines and adult ovines, and suggested that growth stage on glucose turnover rate is probably as important as the effect of animal species.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation